Genetic control of number of days to flowering in dry bean - Santos, João Bosco dos; Vencovsky, Roland (Pesquisa Agropecuaria Brasileira, 2014)
Eight bean (Phaseolus vulgaris L.) cultivars were crossed following a half-diallel model and data were obtained from the parents and F2 generation, in order to determine the genetic control of number of days to flowering. A randomized block design with three replications was used, and the data were analysed considering the dominant-additive method. The data met the assumptions of the model and showed that the additive gene action was predominant in relation to dominance gene action. Consequently, narrow sense heritability was 92, 5% and mean degree of dominance was lower than 1, 0. Due to the predominance of the additive gene action, one should consider the mean of the parents in relation to the number of days to flowering to carry out a breeding program. To obtain early cultivars, the dominance gene action is also important. Among the cultivars studied, the 'Goiano Precoce' showed higher potential to precocity in relation to additive and dominance gene actions.